Factors of Stress Affecting the Academic Performance among the University Students - Lawrence, Nur Sorfina; Aduka, Siti Zunika; Desa, Zalina Mohd (School of Social Sciences, USM, 2017)
Stress is a psychological and physiological response to the demands of the environment and it can be negative or positive one (Votta & Benau, 2014). Those in working environment and university environment face stress in their daily life regardless of age and gender and it could either improve their performance or vice versa. An acceptable amount of stress can improve the students’ performance while an excessive amount of stress will decreased the student academic performance (Anne & Sarah, n.d.). For university students, stress can affect the students’ academic performance badly if students failed to control their level of stress. According to Hirsch & Ellis, 1996; Morgan, 1997, as cited in Messarra, 2005, high level of stress can turn to depression which in several cases may lead to high numbers of suicide attempts. Many researches regarding stress among students had been conducted all around the world but with the current economic condition and high technology advancement in Malaysia, this study will prove whether all the findings by the previous researchers are still relevant. Hence, this study aims to identify the factor of stress faced by university students. Among the factors of stress are academic stress, social stress, financial stress and other minor stressors (Messarra, 2005). Therefore, the objectives of this study are to identify the relationship between academic stress, social stress and financial stress with academic performance, to compare the most dominant factor of stress between genders and to identify the stress relievers taken by students in coping with their stress.